Routing optimization in the internet of vehicle: a systematic review - Ahmed, Zeinab E.; Hassan Abdalla Hashim, Aisha; Saeed, Rashid A.; Elbasheir, Mohammed S. (IEEE, 2024)
The Internet of Vehicles (IoV) represents a novel concept in vehicle communication, seamlessly is integrating cloud computing, the Internet of Things (IoT), and Vehicular Ad-hoc Networks (VANETs). Its popularity has been steadily rising, offering innovative solutions for efficient transportation management. Within a dynamic system replete with moving vehicles, addressing routing problems and related challenges is imperative. Optimal routes necessitate collective decision-making, considering the entire network rather than individual routes. Tackling this complexity, the adoption of optimization techniques becomes pivotal in seeking optimal solutions for intricate issues. This paper undertakes a comprehensive review and discussion of diverse optimization methods applicable to IoV routing protocols.